Nitrogen fertilizer affects starch synthesis to define non-waxy and waxy proso millet quality. (15th February 2023) - Wang, Honglu; Li, Dongmei; Ma, Qian; Wu, Enguo; Gao, Licheng; Yang, Pu; Gao, Jinfeng; Feng, Baili
Abstract: Understanding the effect of nitrogen fertilization on the quality of proso millet is key to expanding the use of this crop to address water scarcity and food security. Therefore, this study determined the impact of nitrogen fertilization on the proso millet quality. Nitrogen fertilization significantly increased the NR and GS activities and decreased the GBSSase activity, resulting in an increase in protein content and reduction in amylose content and L*, which decreased the appearance quality. Nitrogen fertilization increased the proportion of short amylopectin chains, resulting in a more disordered carbohydrate structure, and decreased the proportion of hydrophilic functional groups, contributing to an increase in setback viscosity and decrease in pasting temperature in the waxy (w139) variety. In contrast, the non-waxy (n297) variety exhibited a larger proportion of long amylopectin chains, lower ordered structure and hydrophobic functional groups after nitrogen fertilization, which strengthened the inter- and intramolecular forces of starch colloids. Graphical abstract: Unlabelled Image Highlights: The synthesis of starch and protein was affected by the nitrogen fertilizer. Nitrogen fertilizer tended to synthesize more short amylopectin of waxy variety. Nitrogen fertilizer improved nutritional quality and deteriorated appearance quality. Crystalline structure and functional groups affect proso millet quality. Waxy and non-waxy proso millet was different in starch synthesis and properties of flour.